2017
DOI: 10.1371/journal.pone.0175559
|View full text |Cite
|
Sign up to set email alerts
|

Better than counting seconds: Identifying fallers among healthy elderly using fusion of accelerometer features and dual-task Timed Up and Go

Abstract: Devices and sensors for identification of fallers can be used to implement actions to prevent falls and to allow the elderly to live an independent life while reducing the long-term care costs. In this study we aimed to investigate the accuracy of Timed Up and Go test, for fallers’ identification, using fusion of features extracted from accelerometer data. Single and dual tasks TUG (manual and cognitive) were performed by a final sample (94% power) of 36 community dwelling healthy older persons (18 fallers pai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 57 publications
1
31
0
9
Order By: Relevance
“…In future studies the examination of neural correlates (EEG, fNIRS) are warrant to confirm this relationship and to understand the neurobiology of cognitive impairment and gait decline. Furthermore, although duration is a typical measurement in dual task research, other studies have shown that spatio-temporal features and joint angles are differentially related to dual-task performance (Montero-Odasso et al, 2009 ; Ponti et al, 2017 ). Hence, studies should include adaptive algorithms that quantify kinematic parameters such as step length, stride length, double support duration, head and body movements (Caldas et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In future studies the examination of neural correlates (EEG, fNIRS) are warrant to confirm this relationship and to understand the neurobiology of cognitive impairment and gait decline. Furthermore, although duration is a typical measurement in dual task research, other studies have shown that spatio-temporal features and joint angles are differentially related to dual-task performance (Montero-Odasso et al, 2009 ; Ponti et al, 2017 ). Hence, studies should include adaptive algorithms that quantify kinematic parameters such as step length, stride length, double support duration, head and body movements (Caldas et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Timed Up and Go (TUG) performance test is useful in assessing risk of falls. Recent studies suggest data from an accelerometer, worn during the TUG test, have the potential to improve the ability of this performance test to measure physical function and estimate risk of falls [22,23].…”
Section: Gapsmentioning
confidence: 99%
“…DT-TUG, i.e., TUG performed concomitantly with another task, has been used to increase TUG sensibility. DT-TUG is more sensitive than single-task TUG in identifying frail and prefrail individuals [36,58], impairment in focused attention [10] and fallers [46] in elderly and PPD [56]. The concurrent cognitive task used in DT-TUG in this study consisted of speaking as many words as possible starting with a specific letter (F, S or A) presented at the beginning of test.…”
Section: Dual-task Timed Up To Go Test (Dt-tug)mentioning
confidence: 99%